Mastering software project management : best practices, tools and techniques - Chemuturi, Murali, 1950- (J. Ross Pub., 2010)
This unique guide explains software project management from the standpoint of a software project manager working in a professional software development organization. It covers the subject of software project management in its entirety, including project acquisition and execution with backward linkages to concepts that play a facilitation role in successful project management, such as general management, decision making, people management, motivation, productivity and expectations management. This comprehensive reference provides all the guidance, best practices, tools and techniques needed to master software project management and achieve superior result.